Churches of Greater Mumbai – a physio-cultural appraisal - Braganza, Charlotte; Mukherji, Dipti (Bulletin of Geography. Socio-economic Series, 2013)
Greater Mumbai is a mosaic of diverse languages, cultures and religions. Churches in Mumbai reflect the long association of Mumbai City and Salsette Island which comprise the present day Greater Mumbai. The churches of Greater Mumbai are relics of art, architecture and culture, as well as multi-lingual and religious tolerance. They enjoy a great history which dates back to the 16th century. With the coming of the Portuguese and British, the churches and their surrounding environment have undergone a spatial and temporal change to withstand the needs of the society with increasing population and prevalent intra-urban migration. The contributions of East Indians, Goans, Mangaloreans, Tamilians and Keralites to the progress and development of the Church in the area is immense. The present paper is an attempt to highlight the environmental history of the churches chronologically with sketches and maps. The study also analyses the geographical background and population composition in and around the churches. It brings out the emerging spatial pattern of churches in Greater Mumbai as well as the changes that have taken place over a period of time. Moreover, the paper describes the contribution of sociofugal and sociopetal forces for generating the socio-environmental scenario in the contemporary spatial framework.